T cell epitope redundancy: cross-conservation of the TCR face between pathogens and self and its implications for vaccines and autoimmunity. (3rd May 2016) - Moise, Leonard; Beseme, Sarah; Tassone, Ryan; Liu, Rui; Kibria, Farzana; Terry, Frances; Martin, William; De Groot, Anne S.
ABSTRACT: T cells are extensively trained on 'self' in the thymus and then move to the periphery, where they seek out and destroy infections and regulate immune response to self-antigens. T cell receptors (TCRs) on T cells' surface recognize T cell epitopes, short linear strings of amino acids presented by antigen-presenting cells. Some of these epitopes activate T effectors, while others activate regulatory T cells. It was recently discovered that T cell epitopes that are highly conserved on their TCR face with human genome sequences are often associated with T cells that regulate immune response. These TCR-cross-conserved or 'redundant epitopes' are more common in proteins found in pathogens that have co-evolved with humans than in other non-commensal pathogens. Epitope redundancy might be the link between pathogens and autoimmune disease. This article reviews recently published data and addresses epitope redundancy, the "elephant in the room" for vaccine developers and T cell immunologists.